OPTIMIZATION OF STORE LAYOUTS AND INTERIOR DISPLAY DESIGNS IN INDONESIAN BATIK RETAIL ARCHITECTURE ATMOSPHERE - Putri, Nurul Idzi Lutvi; Ustazah, Eri Naharani; Wardhana, Mahendra (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2025)
The fashion industry has become one of the most influential sectors in Indonesia's economic growth. Batik, as part of the fashion industry, has a sales concept with a retail store system because it is considered to require specific perception stimuli and shopping experiences. In the direct marketing process, one of the most important aspects to consider is atmospheric architecture or environmental atmosphere architecture. Atmospheric architecture involves designing an environment to evoke specific emotional responses in potential buyers, thereby increasing the likelihood of successful product purchases. With the existence of this concept, the atmospheric architecture elements of the environment as decision-making supporters must be studied and optimized. A finding is needed regarding the store atmosphere elements that influence the creation of an optimal shopping ambiance and experience in the batik retail environment. The method used is a qualitative method involving in-depth interviews and photo elicitation. Data processing was carried out using Computer-Assisted Qualitative Data Analysis Software to classify the research findings and was followed by homogeneous validation of the results with the respondents. This finding shows how store layouts and display designs affect sales. It also suggests ways to use these ideas in batik stores to increase product purchases.